Emergency units and COVID-19: Burnout, and empathy reported by nursing professionals and perceived by patients - Daiane Silva Lopes Viana; Julia Yaeko Kawagoe (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To investigate Burnout Syndrome and empathy self-reported by the nursing staff and empathy perceived by the patient. Method: Cross-sectional study in a public emergency unit in São Paulo (from October/2020 to March/2021). The nursing staff answered the Maslach Burnout Inventory and the Consultation and Relational Empathy Measure-Nurses (Brazilian version), whereas adult patients answered the Consultation and Relational Empathy Measure (Brazilian version). Descriptive and inferential analysis, with a 5% significance level. Results: A total of 92 professionals and 271 patients participated. Most professionals reported impact of COVID-19 (80; 86.96%) and, among them, increased Burnout Syndrome (93; 75%), but with low emotional exhaustion (71; 74%), low depersonalization (59; 78%) and high level of professional accomplishment (72; 83%). Most reported impact and increased empathy, and the results reported by professionals and patients (mean and standard deviation) were: 39.89 (6.44) and 38.25 (9.45), respectively. Conclusion: The professionals reported a low level of Burnout Syndrome and a high level of empathy in pandemic.